Caries dental en los menores de veinte años en Colombia: un problema de salud pública (2003)
ABSTRACT: Despite the reduction in the decayed, missing and filled teeth (DMF-T) index on national surveys, dental caries remains the first oral health problem and important cause of morbidity in Colombian children. At the age of 7.18% of children have at least a caries lesion, 57% at the age of 12 and 70.7% in the 15-15 age group. In primary dentition, 60.4% of children experimented the disease by the age of 5. Data are limited under the age of five despite the world wide concern about the persistence of the disease in this group. The disease is not equally distributed; rural areas less developed region and lowest socioeconomic groups show higher prevalence, revealing other preventive approaches are the best long-term option to improve oral health condition in populations. Educational policies of human resources have been carried out in Colombia as well as school programs and water and salt fluoridation. The health system reform has introduced new challenges and has changed existing programs. A change in the attitude towards the disease and the recognition of oral health as a part of general health becomes necessary as well as the redefinition of priority groups, the early definition of promotion programs and the investigation on innovative strategies to improve oral health.